Case report: An intrauterine device hugging the musculus rectus abdominis through the center of a cesarean scar - Jing, Jigang (Frontiers in Surgery, 2023)
A 34-year-old woman presented abscess of abdominal wall with rupture and discharge for 10 days. She had a history of IUD insertion five years with lumbago and abdominal pain four years. She had a history of cesarean section 17 years ago. A "V" shaped IUD was observed ultrasonically between the bladder and abdominal wall, clinging to the musculus rectus abdominis through the center of the cesarean scar. Pelvic computed tomography (CT) revealed a "V" shaped metal density at the anterior upper edge of the bladder, one end of which seemed to penetrate the abdominal wall. IUD migration was confirmed by surgery two days later. The patient recovered after IUD removal. This case affirms that a migrated IUD can lead to serious complications occur even if there are no obvious symptoms for many consecutive years. Apart from the fact that the IUD has fallen off, migrated IUD should be removed promptly regardless of obvious complications. Furthermore, regular ultrasonic examination is an important method for early diagnosis of IUD displacement. Combined with the literature, we hypothesized the possible mechanism of IUD migration between the bladder anterior wall and the abdominal wall.